Remoção de matéria orgânica em sistema francês de wetland construído com leito de segundo estágio parcialmente saturado - Ramos, Renan Ballini (2019)
This final course assignment aimed to operating and monitoring constructed wetland system with submerged vertical flow type French model, implanted as experimental unit to treat raw effluent of University Restaurant on the campus Londrina of UTFPR. The system used Heliconia Rostrata as macrophytes and its structure was consisted of two beds in the first stage and one bed in the second stage. The objective of this study was to verify the removal of organic matter in the treatment, collecting samples and analyzing the parameters: BOD5, COD, total and suspended solids series, turbidity and true color. The removal efficiencies were: 96%, 91%, 60%, 90%, 98% and 54%, respectively, demonstrating viability in the effluent treatment, to the operational conditions adopted, 1,32 m3/m2h to each bed on first stage and 1,5 m3/m2h to the second stage.